A 2.44μs row conversion time 12-bit high-speed differential single-slope ADC with TDC applied to CMOS image sensor. (February 2022) - Gao, Jing; Yan, Ningxi; Nie, Kaiming; Gao, Zhiyuan; Xu, Jiangtao
Abstract: To improve the quantization speed of single-slope (SS) analog-to-digital converter (ADC), a cross-coupling input technique is proposed, which can automatically select the direction of input coupling according to the signal polarity. The proposed SS ADC is implemented and simulated through 110 nm process. The main clock frequency is 125 MHz. The simulation results show that the row conversion time of SS ADC is 2.44 μs, the resolution is 500 ps, and the power consumption is 129–198 μW. It is proved that these techniques can greatly improve the speed of quantization while ensuring power consumption and accuracy.